Evaluation of Learning to Improve The Efficiency of Student Assessment - Kevin Febriyanti; Siti Qoiria; Maurin Diva Ananda (Institut Agama Islam Negeri Sorong, 2022)
Assessment is an activity that is impossible to separate from learning activities in general. Without conducting an assessment, it is impossible for teachers to objectively assess and report student learning outcomes. Assessment of the results of the learning process is carried out by the teacher as an integral part of the process of learning activities. That is, assessment is inseparable in the preparation and implementation of learning. Assessment of learning processes and outcomes aims to assess the effectiveness and efficiency of teaching activities as material for the improvement and improvement of the program and its implementation. The methods used in this study are the critical anlitis method and the literature method. The need for learning evaluation in order to increase student knowledge and have a very remarkable impact on the efficiency of the assessment to be given.